From Invisible to Unstoppable: How AI and Digital Marketing Transform IT Consulting Start-ups - Rym Khanfir (Tecno Scientifica Publishing, 2026)
Information technology consulting start-ups in emerging markets faced considerable challenges in establishing market visibility against well-established competitors, particularly because of limited marketing resources. Although digital marketing and artificial intelligence were increasingly presented as potential solutions, limited empirical evidence had documented their adoption within this sector and context. This study examined how a Tunisian information technology consulting start-up perceived and used digital marketing and artificial intelligence to strengthen its competitive position. Nine semi-structured interviews were conducted with members of the management team, clients, and a prospective client of a company anonymized as AlphaTech Consulting. The interview data were supplemented by a review of the relevant literature and analyzed using the thematic analysis approach proposed by Braun and Clarke. Thematic saturation was reached after the eighth interview. Five principal themes emerged. First, limited digital visibility was perceived as a major competitive constraint. Second, search engine optimization and the production of expert content were regarded as the most sustainable mechanisms for improving visibility. Third, artificial intelligence tools increased the volume, consistency, and frequency of marketing activities without requiring substantial additional resources, although systematic editorial oversight remained necessary. Fourth, a clear tension emerged between automated interactions and the relationship-based requirements of business-to-business consulting. Consequently, the company differentiated between activities managed through digital tools and those requiring direct consultant involvement. Fifth, customer data governance was viewed not merely as a regulatory obligation but also as an important indicator of credibility and trustworthiness. Based on these findings, ten managerial recommendations were developed across three implementation horizons. The study contributed to the literature on artificial intelligence adoption in the marketing practices of business-to-business service-oriented small and medium-sized enterprises in emerging markets by proposing a sequential hybridization model that combined automation with human interaction. The limitations associated with the single-case study design were also acknowledged.